Integrating methodologies for an optimum landscape management. An experience of land-use planning of Morelia, Michoacán (Mexico) - Franch-Pardo, Iván (2018)
This work addresses a proposal for the correct management of the landscape in the municipality of Morelia. It refers to different methodologies of landscape studies traditionally used in Mexico. It concludes with the necessity to make use of methods that integrate the physical and human aspects of the territory, and that they respond to the landscape concepts embodied in Mexican legislation. Firstly, the work territorial units (called Strategic Territorial Units –UTE- according to the  PMGROT) were delimitated and defined by geomorphological criteria. These last ones were based on a methodological approach of great international prestige, such as the Geomorphological Survey of the Dutch School. Subsequently, various landscape analyzes were carried away for the UTEs, which were founded on the postulates of the Landscape european convention, collected by the Latin American Landscape Initiative. The latter ones were the visibility studies (structured in three areas: intrinsic visibility, visual accessibility, and visibility of negative impacts). Finally, key qualities for landscape management were evaluated, such as quality, fragility and landscape capacity. All this allowed the making of substantiated proposals for the management and protection -from a landscape perspective- of the UTE of the municipality of Morelia.